2014
DOI: 10.1002/gps.4170
|View full text |Cite
|
Sign up to set email alerts
|

Translating cognitive and everyday activity deficits into cognitive interventions in mild dementia and mild cognitive impairment

Abstract: This review highlights the need for further translation of the understanding of cognitive and everyday activity deficits into successful interventions for daily activities in MCI and early dementia. Hence, research is first required to link individual activities with cognitive domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 57 publications
(97 reference statements)
0
11
0
Order By: Relevance
“…Personal factors involve the person's (pre-morbid) personality, competencies and skills, life history and important life values, including spiritual values, but also the person's engagement in activities and relationships, his or her sense of usefulness, the awareness of having dementia, and the recognition and acceptance of care needs (Apte, Kielhofner, Paul-Ward, & Braveman, 2005;Ennals & Fossey, 2007;Kielhofner, 2008;Townsend & Polatajko, 2013). Disease-related factors involve dementia-related disabilities in the subsequent stages of the disease, other existing cognitive and physical disabilities, and co-morbidity (Giebel & Challis, 2015;Giebel, Challis, & Montaldi, 2015a;Muo et al, 2005).…”
Section: Influencing Factorsmentioning
confidence: 99%
“…Personal factors involve the person's (pre-morbid) personality, competencies and skills, life history and important life values, including spiritual values, but also the person's engagement in activities and relationships, his or her sense of usefulness, the awareness of having dementia, and the recognition and acceptance of care needs (Apte, Kielhofner, Paul-Ward, & Braveman, 2005;Ennals & Fossey, 2007;Kielhofner, 2008;Townsend & Polatajko, 2013). Disease-related factors involve dementia-related disabilities in the subsequent stages of the disease, other existing cognitive and physical disabilities, and co-morbidity (Giebel & Challis, 2015;Giebel, Challis, & Montaldi, 2015a;Muo et al, 2005).…”
Section: Influencing Factorsmentioning
confidence: 99%
“…Giebel and Challis (2015) searched the literature in May of 2013 and found only three cognitive intervention studies in MCI that had an everyday functional ability outcome. These authors noted that while these three studies were encouraging that cognitive training could improve ADLs in MCI, the studies lacked clear descriptions of the interventions, apparent non-standardized administration of the interventions, and weak theoretical rationale for choice of cognitive strategy.…”
Section: Introductionmentioning
confidence: 99%
“…By understanding which IADLs are mostly impaired, interventions can target these IADLs specifically. In particular, a recent review on the efficacy of cognitive interventions for everyday activities showed that targeting individual activities, rather than global functioning, is more efficacious (Giebel and Challis, 2015).…”
Section: Introductionmentioning
confidence: 99%